Effect of Salt (Sodium Chloride) Replacement With Potassium Chloride, High Pressure Processing, and Cold Storage at 4°C on Beef Sausage Volatile Compounds - Ojangba, Theodora; Zhang, Li; Boamah, Solomon; Gao, Yanlei; Wang, Zhuo; Alhassan, Martha Wunnam (Frontiers in Nutrition, 2022)
This study aimed to investigate the partial substitution of 0%, 25%, and 50% sodium chloride (NaCl) by potassium chloride (KCl) coupled with high-pressure processing (HPP) effects on volatile compounds and lipid oxidation of beef sausage at five (0, 3, 7, 14, and 21) different cold storage days (4 ℃). The odor activity values (OAV) of the compounds were visualized by heat map analysis. Thiobarbituric acid reactive substances (TBARS) of the samples treated with 100% NaCl and HPP increased by an average of 0.52±0.01 mg MDA/kg compared with the control across the 21 storage days. In addition, 50% NaCl substitution with KCl in combinations with HPP treatments increased TBARS across the 21 storage days by an average of 0.40±0.02 mg MDA/kg compared with no HPP treatment. However, on day 3, there was a sharp decrease in TBARS by an average of 0.10±0.01 mg MDA/kg compared with days 0, 7, 14 and 21 in all treatments. At the end of 21 days of storage, a total of 227 volatile compounds were identified and quantified in the beef sausage, including 43 aldehydes, 46 phenols, 8 ketones, 30 alcohols, 14 acids, 12 esters, 27 terpenes, and 47 alkanes. However, no ketone compounds were detected on days 7, 14 and 21; esters on day 14 and acids on days 14 and 21 in the samples treated with or without HPP across the salts levels. However, high OAVs (OAV > 1) were obtained after partial substitution of NaCl with KCl at 25% and 50% with HPP treatment compared to the samples not treated with HPP. The aroma perceived in the beef sausage was due to compounds with the highest OAVs such as; pentadecanal, benzyl carbazate, anethole, myristicin, o-cresol, phenylacetaldehyde and (E)-methyl isoeugenol, pentadecanal, hexanoic acid, octanoic acid, eugenol, trans-2-nonenal, trans-2-octenal, trans-2-decenal, 2-butyl-1-octanol, 2,3-butanedione, ethyl hexanoate, ethyl octanoate, (-)-4-terpineol which had an OAV>1 as compared to the other compounds with an OAV<1. In conclusion, 25% and 50% NaCl partial replacement with KCl coupled with HPP technique can be considered in producing low-NaCl beef sausage in order to improve the flavor and decrease lipid oxidation during cold storage.